(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Network-on-Chip (NoC) has been proposed as a viable solution to the communication challenges on System-on-Chips (SoCs). As the communication paradigm of SoC, NoCs performance depends mainly on the type of routing algorithm chosen. In this paper different categories of routing algorithms were compared. These include XY routing, OE turn model adaptive routing, DyAD routing and Age-Aware adaptive routing. By varying the load at different Packet Injection Rate (PIR) under random traffic pattern, comparison was conducted using a 4 × 4 mesh topology. The Noxim simulator, a cycle accurate systemC based simulator was employed. The packets were modeled as a Poisson distribution; first-in-first-out (FIFO) input buffer channel with a depth of five (5) flits and a flit size of 32 bits; and a packet size of 3 flits respectively. The simulation time was 10,000 cycles. The findings showed that the XY routing algorithm performed better when the PIR is low. In a similar vein, the DyAD routing and Age-aware algorithms performed better when the load i.e. PIR is high.